Voluntary Disenrollment from Medicare Advantage Plans Is Higher Among Racial and Ethnic Minorities - Martino, S.C. (Health Serv Res, 2020)
RESEARCH OBJECTIVE: About one‐tenth of Medicare Advantage (MA) enrollees voluntarily disenroll from their health plans annually. Voluntary disenrollment is related to beneficiaries’ negative experiences with their plan, disrupts continuity of care, and conflicts with goals to reduce Medicare costs. Research on racial and ethnic differences in voluntary disenrollment is important, as it may inform efforts to reduce racial and ethnic disparities in care. The few prior studies of this topic have had significant limitations, including reliance on administrative data on race and ethnicity that are often missing or inaccurate, failure to control for potential confounding variables such as dual eligibility for Medicare and Medicaid, and use of data that is more than 20 years old. Our investigation of racial and ethnic differences in rates of disenrollment from MA plans overcomes these limitations. STUDY DESIGN: Disenrollment data came from Medicare’s enrollment system. Social Security Administration data on race and ethnicity were augmented with surname, address, and other Medicare administrative data to calculate probabilities of membership in different racial and ethnic groups. We summarized differences in rates of disenrollment across racial and ethnic groups (Asian or Pacific Islander [API], black, Hispanic, and white) using four types of logistic regression models: adjusted and unadjusted models estimating overall differences and adjusted and unadjusted models estimating within‐plan differences. Unadjusted overall models included only racial and ethnic group probabilities as predictors. Adjusted overall models added age, gender, dual eligibility, disability, and state of residence as control variables. For each model, we calculated the difference from whites for each racial and ethnic minority group. We also estimated differences in disenrollment rates that are attributable to within‐plan effects. Between‐plan differences were estimated by subtracting within‐plan differences from overall differences. POPULATION STUDIED: 16 770 319 Medicare beneficiaries enrolled in 736 MA plans nationwide in 2015. PRINCIPAL FINDINGS: Adjusted rates of disenrollment were significantly (P < .001) higher for Hispanic (+1.2 percentage points), black (+1.2 percentage points), and API beneficiaries (+2.4 percentage points) than for whites. Within states, all three racial and ethnic minority groups tended to be concentrated in higher‐disenrollment plans. More than 70% of the adjusted overall difference between API and white beneficiaries reflected API beneficiaries’ tendency to disenroll from the same plans at markedly higher rates than white beneficiaries. CONCLUSIONS: We identified higher rates of voluntary disenrollment from MA plans for racial and ethnic minorities than for whites, even after controlling for factors such as dual eligibility and disability, which relate to both disenrollment and race and ethnicity. These differences exist partly because racial and ethnic minorities are more concentrated in plans with higher overall disenrollment rates and partly because of higher within‐plan disenrollment rates, particularly among API beneficiaries. IMPLICATIONS FOR POLICY OR PRACTICE: Racial and ethnic minorities may require additional—or different—assistance with plan selection than what whites need, as well as improved access to low‐disenrollment plans. Getting to the root of higher voluntary disenrollment rates for racial and ethnic minorities could improve the MA marketplace as well as the care of racial and ethnic minority beneficiaries. PRIMARY FUNDING SOURCE: Centers for Medicare and Medicaid Services.